증강현실 자막 콘텐츠 표시에 대한 휴먼팩터 평가 - 김대연 (한국멀티미디어학회, 2022)
In this study, the effect of augmented reality subtitle content on users was investigated by using a subjective evaluation method and a statistical approach. The human factor was defined as subtitle position and font size. Then, we analyzed the effects of the defined factors on human eye comfort and visibility. Ten participants conducted related survey evaluation tasks with a 1-minute break after viewing the content for 3 minutes.